Clinical and metabolic profile of adults with obesity attending lifestyle medicine clinics - Hanan N. AlTaib; Reem AlAqeel; Amr A. Arafat; Faisal Kunnathodi; Abdulmajeed AlShaikh; Haifa F. AlOtaibi (PLoS ONE, 2026)
Background Lifestyle Medicine Clinics (LMCs) in primary care provide structured, multidisciplinary obesity care, but evidence from Saudi Arabia on patient profiles and the effectiveness of pharmacologic therapy in this setting is limited. Methods We conducted a retrospective cohort study at a primary health care center in Prince Sultan Military Medical City, Riyadh (2023–2024). Adults aged 18–75 years with Body Mass Index (BMI) 30–40 kg/m² and at least one obesity-related comorbidity were included. Patients received either Liraglutide plus lifestyle modification or lifestyle modification alone. Data from the LMCs electronic registry were analyzed after 1:1 propensity score matching. Within-group changes were evaluated using paired tests; between-group differences over time were analyzed using repeated-measures ANOVA. Results Among 664 patients (299 receiving Liraglutide and 365 receiving lifestyle modification alone), 280 matched pairs were analyzed (median age 40 years; 73% female). Both groups achieved significant within-group reductions in BMI, systolic and diastolic blood pressure, and HbA1c (all p < 0.05). Between-group comparisons showed a statistically significant difference only in waist circumference change (p = 0.03). Mean BMI change was − 0.75 kg/m² with Liraglutide versus − 0.71 kg/m² without Liraglutide (p = 0.939). No significant between-group differences were observed for glycemic control, blood pressure, or lipid parameters. Conclusions In a real-world primary care setting, Liraglutide plus lifestyle modification and lifestyle modification alone both produced a substantial benefit in metabolic and anthropometric parameters. The incremental benefit of Liraglutide was confined to a modest reduction in waist circumference and did not translate into clinically meaningful differences compared with lifestyle intervention alone. Structured, multidisciplinary lifestyle care should remain the foundation of obesity management, with pharmacotherapy targeted to selected patients.